J'Accuse! - Seldon, Anthony (New Statesman, 2019)
The article discusses the political background leading to the referendum for a British exit from the European Union (EU), known as Brexit. Topics include public opinion about British Prime Minister Theresa May, British national identity in relation to social conflict regarding Brexit, and the lack of potential political leaders to serve as prime minister in the future.